Comprehensive Physicochemical Characterization of Gambier Leaf Extract-Modified Layered Double Hydroxide - Jefri, Jefri; Erviana, Desti; Syafa Aliyah, Amanda (Magister Program of Material Science Graduate School of Universitas Sriwijaya, 2026)
Layered double hydroxide (LDH) is a promising material; however, its application is still limited by agglomeration and suboptimal physicochemical properties. In this study, Ni–Al LDH was modified with Uncaria gambir leaf extract via coprecipitation to improve its properties. Characterization using FT-IR, XRD, BET, SEM/TEM, XPS, and UV–DRS showed that the layered structure of LDH was retained after modification, while significant changes in surface chemistry resulted from the introduction of phenolic groups. Interaction between the extract and LDH occurs primarily at the surface via hydrogen bonding and π–π interactions. Optical analysis revealed a decrease in the bandgap energy from 2.32 eV to 1.32 eV, indicating increased visible-light absorption. Textural properties revealed a decrease in surface area due to pore closure and increased agglomeration. Nevertheless, the presence of active groups from the extract enhances the material’s reactivity and interaction potential. These results demonstrate that gambier extract effectively modifies the physicochemical properties of LDH, providing a strategy for developing sustainable biomass-based hybrid materials.